Studies of the Cabibbo-suppressed decays D+ → π0ℓ+v and D+ → ηe+ve - Bartelt, J; Csorna, SE; Jain, V; Marka, S; Freyberger, A; Godang, R; Kinoshita, K; Lai, I; Pomianowski, P; Schrenk, S; Bonvicini, G; Cinabro, D; et al. (1997)
Using 4.8 fb-1 of data taken with the CLEO II detector, the branching fraction for the Cabibbo suppressed decay D+ → π0ℓ+v measured relative to the Cabibbo favored decay D+ → K0̄ℓ+v is found to be 0.046 ± 0.014 ± 0.017. Using Vcs and Vcd from unitarity constraints, we determine |fπ+(0) / fK+(0)|2 = 0.9 ± 0.3 ± 0.3 We also present a 90% confidence level upper limit for the branching ratio of the decay D+ → ηe+ve relative to that for D+ →0e+ve of 1.5. © 1997 Published by Elsevier Science B.V.